2009
DOI: 10.2320/matertrans.m-m2009804
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of Large Scorodite Particles from Aqueous Fe(II) and As(V) Solution by Oxygen Injection

Abstract: A novel method for synthesizing large scorodite (FeAsO 4 . 2H 2 O) particles was recently developed for the fixation of arsenic. This method involves the coprecipitation of scorodite particles from an Fe(II) and As(V) aqueous solution at approximately 95 C by oxygen injection. In order to understand the process of coprecipitation of scorodite particles by this method, X-ray diffractometry (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) were used for characterizing reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The gel-like precursor is consumed and it is not observed in latter stage of scorodite formation. Shinoda et al 11) analyzed the chemical state of iron in the gel-like precursor by X-ray absorption near-edge structure (XANES) spectroscopy at the Fe K absorption edge. According to their results, the gel-like precursor mainly consists of Fe(II) with a small amount of Fe(III).…”
Section: Introductionmentioning
confidence: 99%
“…The gel-like precursor is consumed and it is not observed in latter stage of scorodite formation. Shinoda et al 11) analyzed the chemical state of iron in the gel-like precursor by X-ray absorption near-edge structure (XANES) spectroscopy at the Fe K absorption edge. According to their results, the gel-like precursor mainly consists of Fe(II) with a small amount of Fe(III).…”
Section: Introductionmentioning
confidence: 99%
“…Shinoda et al 23) used X-ray absorption near-edge structure spectroscopy to investigate the chemical state of Fe in the gel-like precursor. Their results showed that the precursor mainly consists of Fe(II) with a small amount of Fe(III).…”
Section: Introductionmentioning
confidence: 99%
“…Scorodite (FeAsO 4 1 2H 2 O) is a promising material for the storage of concentrated arsenic generated by copper smelting. 1) Scorodite can be synthesized from a sulfuric acidic solution containing bivalent iron [Fe(II)] and pentavalent arsenic [As(V)] via oxidation under flowing O 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…4) Monitoring the growth process with scanning electron microscopy (SEM) revealed that the precursor agglomerated during the early stage of scorodite synthesis. 9,10) As reaction time increased, the agglomerates were transformed to scorodite by the crystal growth during further oxidation.…”
Section: Introductionmentioning
confidence: 99%